Internationalization and medium-level technical professional education: study of the partnership between Ceeteps and Icif (Research, Society and Development, 2021)
The present work refers to the challenges of internationalization for the technological axis of Tourism, Hospitality and Leisure regarding the diffusion, promotion, benefits and obstacles of international cooperation between institutions of professional and technological education, the State Center for Technological Education Paula Souza (Ceeteps) and the Italian Culinary Institute for Foreigners (Icif). Concurrent with the development of the internationalization of education and all the processes that involve globalization and the most diverse interests, it is important to understand the needs, relationships and ways of preparing students for the world of work. The focus of this research is centered on the courses of the Technological Axis of Tourism, Hospitality and Leisure, from Etec Santa Ifigênia, located in the city of São Paulo and whose differential is that in its conception it is a core of excellence in hospitality. This Hospitality Center is the result of an international partnership agreement between Ceeteps and Icif.